2023
DOI: 10.1002/smll.202301114
|View full text |Cite
|
Sign up to set email alerts
|

Surface Self‐Transforming FeTi‐LDH Overlayer in Fe2O3/Fe2TiO5 Photoanode for Improved Water Oxidation

Abstract: Integrating hematite nanostructures with efficient layer double hydroxides (LDHs) is highly desirable to improve the photoelectrochemical (PEC) water oxidation performance. Here, an innovative and facile strategy is developed to fabricate the FeTi‐LDH overlayer decorated Fe2O3/Fe2TiO5 photoanode via a surface self‐transformation induced by the co‐treatment of hydrazine and NaOH at room temperature. Electrochemical measurements find that this favorable structure can not only facilitate the charge transfer/separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The improvement of stability is a subject worth exploring in detail, and a stable semiconductor heterojunction or a passivation layer can improve stability. 48,49…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of stability is a subject worth exploring in detail, and a stable semiconductor heterojunction or a passivation layer can improve stability. 48,49…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the charge transfer processes at the photoanode/electrolyte interface, electrochemical impedance spectroscopy (EIS) measurements were performed in the dark (Figure b). The Nyquist plots displayed characteristic shapes with two semicircles, and the results were fitted using an equivalent circuit model (inset of Figure b and Table S4), where R s represents the series resistance, R trap represents the charge transfer resistance in the bulk of the photoanode, and R ct reflects the charge transfer resistance at the electrode/electrolyte interface. , The fitting results showed that the series resistance remained nearly unchanged, while the decrease in R trap after Ru loading can be attributed to the enhanced conductivity of the photoanode due to the partial doping of Ru into Fe 2 O 3 . Importantly, R ct was significantly reduced from 145.6 Ω for Fe 2 O 3 to 54.3 Ω for Fe 2 O 3 –Ru, indicating that the loading of Ru facilitates the injection of photogenerated carriers into the electrolyte for the water oxidation reaction.…”
mentioning
confidence: 99%
“…The Nyquist plots displayed characteristic shapes with two semicircles, and the results were fitted using an equivalent circuit model (inset of Figure 4b and Table S4), where R s represents the series resistance, R trap represents the charge transfer resistance in the bulk of the photoanode, and R ct reflects the charge transfer resistance at the electrode/ electrolyte interface. 41,42 The fitting results showed that the series resistance remained nearly unchanged, while the decrease in R trap after Ru loading can be attributed to the enhanced conductivity of the photoanode due to the partial doping of Ru into Fe Remarkably, after incorporating Ru, the carrier density of Fe 2 O 3 −Ru was found to be nearly ten times higher than that of Fe 2 O 3 , underscoring the significant enhancement in the photoanode's conductivity. To further evaluate the active sites, the electrochemically active surface area was assessed (Figures 4d and S15) by determining the electrochemical double-layer capacitance (C dl ) from cyclic voltammograms (eq S4).…”
mentioning
confidence: 99%